Commodity dependence, global commodity chains, price volatility and financialisation: Price-setting and stabilisation in the cocoa sectors in Côte d'Ivoire and Ghana - Bernhard Tröster; Cornelia Staritz; Jan Grumiller; Felix Maile (Austrian Foundation for Development Research (ÖFSE), 2019)
Commodity price volatility remains a crucial development challenge of commodity-dependent countries of the Global South. Drawing on structural development economics' concerns with commodity price volatility and stabilisation, this article calls for the integration of price-setting into the analysis of governance in global commodity chains (GCCs). It argues that price-setting power and related uneven exposure to price instability and risks adds to other power dimensions in producing unequal distributional outcomes in GCCs. The paper assesses national price stabilisation in the top cocoa-producing countries Côte d'Ivoire and Ghana against changing inter-firm governance and price-setting institutions in the cocoa GCC. Based on over 50 interviews with commodity trading houses (CTHs) and cocoa sector actors in Côte d'Ivoire and Ghana, our analysis shows that national-level price stabilisation mechanisms address intra-seasonal producer price volatility, but have few possibilities to shield export and producer prices from inter-seasonal price variations. This is because both countries remain 'global price takers' with global prices set on financialized derivatives markets and transmitted along the GCC by CTHs, which limits possibilities for 'domestic price making'. This leaves the major burden of price risks between seasons with smallholder producers that have the least possibilities to deal with these risks.
Keywords: 330; Global Commodity Chains; Cocoa; Commodity Trading Houses; Price Setting; Financialisation; Côte d'Ivoire; Ghana